0667 Learning To Phenotype RLS From Zappelphilipp (Fidgety Philip) Cartoons. (27th April 2018) - Hussaina, H; Tse, E; Beyzaei, N; Maher, K S; Bao, S; Campbell, M; Carson, N; Garn, H; Kohn, B; Lee, Y; Van der Loos, M; Stockler, S; et al.
Abstract: Introduction: Individuals with neuropsychiatric and/or neurodevelopmental conditions often display disruptive behaviours such as hyperkinesia, hypermotor-restlessness, hyper/hypo-arousability and hypermotor events (H-behaviours). This terminology, introduced by the Video-Working-Group of the International Paediatric Sleep Association (IPSA), allows for a neutral, training background independent, in-depth phenotyping of structured behavioural observations. As a first step, we investigated how to develop a shared, neutral, annotation language for describing and not interpreting H-behaviours, using qualitative open-ended and pictogram-based annotations (O-a; P-a). Methods: Using REDCap data collection software, seven research assistants without prior formal training analyzed: (A) three 'Fidgety Philip' (FP) cartoons, using qualitative O-a and reviewed possible applications for P-a. (B) Then, 12 Suggested Clinical Immobilization Test (SCIT) video snapshots of five participants were analyzed using O-a and the exercise was repeated 2 days later, in a randomized order; the same 2-day procedure was repeated using P-a. (C) Inter-/Intra-observer variability of (A) & (B) results was investigated. Results: (A) FP-cartoons: O-a were divided into descriptions (n=168, mean=8.0 ± 3.8) and interpretations (n=106, mean=5.0 ± 3.1); with each cartoon, the number of descriptions increased compared to interpretations. (B) SCIT snapshots: Day 1 & 2 data were separated into descriptive vs. interpretive results: O-a (median=6/7 vs. median=1/1) and P-a (median=1/2 vs. median=2/1); then pictogram categorization was reassessed and developed further. (C) Intra-observer reliability for descriptive/interpretative O-a was low (descriptive statistics: 61.9%/36.6%). Inter-observer reliability of P-a for overarching categories was higher (intraclass correlation coefficients: head 0.895; upper limbs: 0.823; lower limbs: 0.878) but low for body tension in dependency of posture (0.588). Conclusion: (A) and (B) With experience, the ability to describe and reduce interpretations increased, P-a enhanced this process. (C) Descriptions yielded low and high inter-observer consistency via O-a and P-a, respectively. P-a characterizing movements achieved higher inter-observer consistencies, while those characterizing body posture and interpretative movements were low. This exercise has: (1) provided feedback for software developers to further adapt the annotation software; (2) created the framework for describing disruptive behaviours using a neutral annotation language, and (3) was integrated into the IPSA-Video-Annotation-Training-Module. Support (If Any): BC Children's Hospital Research Institute and Foundation.